2017
DOI: 10.2147/ott.s147438
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and safety of combined <em>BRAF</em> and MEK inhibition in patients with malignant melanoma: a meta-analysis

Abstract: BackgroundRecent clinical studies have shown that initial therapy with combined BRAF and mitogen-activated extracellular signal-regulated kinase (MEK) inhibition is more effective in metastatic melanoma than single-agent BRAF inhibitors. However, the response rates with single-agent BRAF are low. Thus, the objective of this study was to conduct a meta-analysis of randomized controlled trials to compare the efficacy and adverse events risk between mono-therapy and combination therapy.Materials and methodsSearch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, dose-limiting side effects are observed, and MEK inhibitors that reduce ERK activation in patients show a low clinical response, probably because MEK inhibition promotes an imbalanced compensatory cell signaling that reduces the therapeutic value of these drugs. Several groups have found that BRAF inhibitor-resistant melanoma cell lines can recover ERK phosphorylation independently of the presence of BRAF inhibitors, and the same remains true for the classic chemotherapeutic drug dacarbazine (DTIC) ( 11 , 13 , 17 , 18 , 20 24 ). For these reasons, the development of novel small molecules that could counteract resistance mechanisms constitutes a first line of research in the melanoma field.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, dose-limiting side effects are observed, and MEK inhibitors that reduce ERK activation in patients show a low clinical response, probably because MEK inhibition promotes an imbalanced compensatory cell signaling that reduces the therapeutic value of these drugs. Several groups have found that BRAF inhibitor-resistant melanoma cell lines can recover ERK phosphorylation independently of the presence of BRAF inhibitors, and the same remains true for the classic chemotherapeutic drug dacarbazine (DTIC) ( 11 , 13 , 17 , 18 , 20 24 ). For these reasons, the development of novel small molecules that could counteract resistance mechanisms constitutes a first line of research in the melanoma field.…”
Section: Introductionmentioning
confidence: 91%
“…Many patients are excluded from novel therapies only because of fast high-speed progression of the disease before a clinical positive response can be expected ( 9 , 10 ). Taken these facts together, consensus exists in the field suggesting that significant improvements of the overall survival rates of melanoma cohorts require an initial fast response to treatment as an inclusion condition ( 11 ). Long-term survival could then be achieved by an increased rate of complete responses or long-term stabilization of partial responses in what is defined in the melanoma field as consolidation phase ( 2 , 7 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of these mutated genes allowed to develop new therapeutic approaches using selective inhibitors for such altered proteins. Promising results were achieved by the treatment with BRAF inhibitors alone or in combination with MEK inhibitors ( Chen et al, 2017 ; Russo et al, 2017 ). However, the identification of effective biomarker of therapeutic response is still lacking ( Masucci et al, 2017 ; Branca et al, 2018 ; Ross et al, 2018 ; Veenstra et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%